The Urgency Of Registering Marriage Agreements For Husband And Wife (Study At The Population And Civil Registry Office Of Medan City) - Mhd. Ridho Eko Prasojo (jurnal.unprimdn.ac.id, 2025)
Registration of Marriage Agreement is a series of marriage implementation. Therefore, marriage registration is an inseparable part of the implementation of the marriage in question (husband and wife). Marriage agreements experienced a shift when there was Constitutional Court Decision No. 69 / PUU-XIII / 2015, namely: